The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/jcad.12062
|View full text |Cite
|
Sign up to set email alerts
|

A Phenomenological Inquiry of Clients’ Meaningful Experiences in Counseling With Counselors‐in‐Training

Abstract: This study is a follow‐up to Sackett, Lawson, and Burge's (2012) study that explored the meaningful experiences of clients and counselors‐in‐training (CITs). Using the previous study's themes of clients’ experiences in counseling with CITs as a launching pad, the authors examined in greater depth the meaningful experiences of clients who are in counseling with CITs through qualitative phenomenological interviews. Findings, as well as implications for counselor education, supervision, and counseling, are discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(57 citation statements)
references
References 25 publications
7
48
0
2
Order By: Relevance
“…To examine clients' meaningful experiences in counseling, we sought sustained engagement by interviewing clients immediately following two consecutive counseling sessions. As did Sackett and Lawson (2016), we used significance sampling to identify meaningful experiences of clients in counseling, which is preferred in exploratory research and involves the examination of units that have noteworthy meaning or therapeutic impact to the participants (Elliott & James, 1989). At each interview, similar to Sackett et al (2012) and to Sackett and Lawson (2016), we used questions about a single counseling session (i.e., two sessions and two interviews) and about within-session meaningful events and session impact, as recommended by Elliott and James (1989).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine clients' meaningful experiences in counseling, we sought sustained engagement by interviewing clients immediately following two consecutive counseling sessions. As did Sackett and Lawson (2016), we used significance sampling to identify meaningful experiences of clients in counseling, which is preferred in exploratory research and involves the examination of units that have noteworthy meaning or therapeutic impact to the participants (Elliott & James, 1989). At each interview, similar to Sackett et al (2012) and to Sackett and Lawson (2016), we used questions about a single counseling session (i.e., two sessions and two interviews) and about within-session meaningful events and session impact, as recommended by Elliott and James (1989).…”
Section: Methodsmentioning
confidence: 99%
“…They found the following themes: the counseling relationship, insight, immediacy, goals, emotion, and reflections on counseling. In a follow-up study, Sackett and Lawson (2016) interviewed adult clients directly after two counseling sessions (i.e., after the second and eighth counseling sessions, when possible). They identified two themes regarding clients' meaningful experiences in counseling with CITs: (a) the working alliance and its impact and (b) impressions of counseling and of CITs.…”
Section: Explored What 12 Adultmentioning
confidence: 99%
“…Diğer açıdan Milli Eğitim Bakanlığı Rehberlik Hizmetleri Yönetmeliği (2017) incelendiği zaman rehber öğretmenlerden öğrencilere yönelik kişisel-sosyal, eğitsel ve mesleki rehberlikle ilgili çalışmalar planlaması ve bu çalışmaları okul rehberlik hizmetleri yıllık planına göre yürütmesi beklenmektedir. Aynı şekilde alan yazındaki rehber öğretmene ilişkin algıların değerlendirildiği bazı araştırmalarda da rehber öğretmenlerden öğrencilere yönelik eğitsel, kişisel-sosyal ve mesleki konularda yardımcı olmalarının beklendiği sonuçlarına ulaşılmıştır (Aydın, 1987;Madlambayan, 2017;Sackett, Farmer ve Moran, 2018;Polat, 2007;Vail, 2005). Görüldüğü üzere rehber öğretmenlere, öğrencilerin ihtiyaç duydukları konularda bilgi veren ve yol gösteren şeklinde rol ve sorumlulukların yüklendiği görülmektedir.…”
Section: Bilgi Veren/yararlı/yol Gösterici Rehber öğRetmen Temasıunclassified
“…Yine aynı şekilde Uğurlu ve Yazıcı (2016) tarafında yapılan bir çalışmada lise öğrencilerinin rehber öğretmeni bilgi veren kişi olarak nitelendirdikleri sonucuna ulaşmışlardır. Yapılan bir diğer çalışmada (Sackett, Farmer ve Moran, 2018) lise öğrencilerinin rehber öğretmeni yardımsever, yararlı, bilgili ve etkili olarak algıladıkları sonucu elde edilmiştir. Öğrencilerin rehber öğretmen kavramına ilişkin algılarının değerlendirildiği başka çalışmalarda da benzer sonuçlara ulaşılmıştır (Karataş ve Sönmez, 2019;Nas, 2019;Yalçın, Yılmaz ve Karakaya, 2017).…”
Section: Tartişma Sonuç Ve öNeri̇lerunclassified
“…For example, I encourage authors to submit works that elucidate the experiences of clients or counselors during or after intervention. A strong example of this type of scholarship is Sackett and Lawson's () qualitative study of clients' reported experiences of counseling as delivered by counselors‐in‐training. I also encourage authors to submit manuscripts that describe client outcomes after exposure to well‐designed interventions, with a particular priority on preventive and culturally responsive counseling services.…”
mentioning
confidence: 99%